The Effect of Immigration Enforcement on School Engagement: Evidence From 287(g) Programs in North Carolina - Laura Bellows (SAGE Publishing, 2021)
During the past 15 years, immigration enforcement increased dramatically in the U.S. interior. There is a growing recognition that immigration enforcement in the U.S. interior has spillover effects onto U.S. citizens. I examine the impacts of a type of partnership between Immigration and Customs Enforcement and local law enforcement, 287(g) programs, on school engagement within North Carolina. In North Carolina, nine counties were approved to establish 287(g) programs, and another 15 applied but were not approved to participate. I use a triple difference strategy in which I compare educational outcomes for different groups of students in these two sets of counties before and after activation of 287(g) programs between 2003/2004 and 2012/2013. I find that 287(g) programs decrease school engagement by decreasing attendance. This effect appears to be driven by increabes in chronic absenteeism (missing 15 or more days per year).